INFLUENCE BIG FIVE PERSONALITY TO HAPPINESS FOR STUDENTS FROM MALUKU IN MALANG - Nani, Firhani Rasni Lestaluhu (PT. Jurnal Center Indonesia Publisher, 2025)
This research aims to see the effect big five personality to happiness to students from Maluku in Malang. The research subjects were 32 people who were students from Maluku and were studying in the city of Malang, aged 19 - 27 years. The research instrument uses a Likert scale, namely Big Five Inventory (BFI) to measure big five personality And Oxford Happiness Questionnaire (OHQ) to measure happiness. After testing, the results obtained were not significant (sig = 0.130>0.05), which means that big five personality does not affect happiness to students from Maluku in Malang. Apart from that, the role percentage big five personality in influencing happiness only 7.5%, while the rest is influenced by other factors.